Strategi Promosi Sales Force Add On Banjarmasin Dalam Meningkatkan Penjualan Produk Indihome Witel Kalimantan Selatan - Damaisari, Rika; H, Husnurrofiq; A, Abdurrahim (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research has two main objectives. The first objective is to find out the promotional strategy of the Banjarmasin Sales Force Add On in increasing sales of IndiHome Witel South Kalimantan products. Meanwhile, the second objective is to understand the concept of the Banjarmasin Sales Force Add On promotional strategy in order to increase sales of IndiHome Witel South Kalimantan products. This research uses descriptive qualitative research with data collection methods through observation, interviews, and documentation. Data analysis was carried out using the analytical descriptive method version of Miles and Huberman (2014) which involved three stages, namely data reduction, data presentation, and drawing conclusions or verification. The results of this study reveal several Sales Force Add On Banjarmasin promotional strategies that have been found, including: 1. Digital advertising campaigns 2. Referral programs 3. Collaboration with local business partners 4. Local exhibition and event activities In addition, this research also identifies several concepts of the Sales Force Add On Banjarmasin promotional strategy that can increase sales of IndiHome Witel South Kalimantan products, including: 1. Market segmentation 2. Personalization of communication 3. Featured benefits 4. Monitoring and measurement of results In conclusion, this research provides insight into promotion strategies Sales Force Add On Banjarmasin which is effective in increasing sales of IndiHome products in the South Kalimantan region.